Menggali Nilai-nilai Toleransi dalam Al-Qur’an dan Urgensinya dalam Kehidupan Bermasyarakat: Aplikasi Pendekatan Ma‘nā cum Maghzā pada QS. Al-Kāfirūn (109): 1-6 - Jamilah, Imroatun (IAIN Madura, 2023)
Humans as social beings need to have a tolerant attitude to differences of ethnicity, culture, language, and religion because tolerance leads to good relations in social life, a peaceful and harmony life. However, in reality, differences often lead to intolerance, causing conflict and hostility. This problem becomes a basis for studying and exploring the values of tolerance in the Qur’an so that it can be understood and applied in everyday life. One of the surahs that contains the values ​​of religious tolerance is QS. al-Kāfirūn (109): 1-6. By using the hermeneutic approach of ma'nā-cum-maghzā theory, it can be concluded that: (1) humans are equipped with a mind and heart, thus, it needs to be utilized optimally so that human life can run well; (2) there will be no benefit for humans when aqidah or belief is obscured; (3) fellow human beings must respect each other and respect all differences. This attitude creates a life of peace and harmony, so that humans avoid conflict and hostility; and (4) preaching properly without coercion whicht is not justified in the Qur'an.